The next public administration debates & dilemmas - Peters, B. Guy; Pierre, Jon (SAGE, 2018)
Critically reviewing the modernization of public management reform, this book explores the past, present and future of public administration. It reasserts public administration as an integral component of democratic governance and fostering a state-citizen relationship. Wide-ranging in scope, The Next Public Administration: extends basic public administration to consider issues associated with management, governance and democracy; covers core public administration concepts and their evolution through time; draws on an international spread of examples, bringing theoretical discussions to life; includes lists of further reading--Back cover.